2020
DOI: 10.5999/aps.2019.01305
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical application of cryolipolysis in Asian patients for subcutaneous fat reduction and body contouring

Abstract: Background Cryolipolysis, a preferred method for minimally invasive body contouring, involves the noninvasive cooling of adipocytes to induce lipolysis without damaging other tissues. This study aimed to evaluate the safety and efficacy of cryolipolysis for the treatment of excessive fat tissue. Methods Between May 2014 and December 2017, 231 patients with 448 areas of interest were enrolled and their records were retrospectively reviewed. We used five different vacuum applicators, and the best-fitting applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 25 publications
(36 reference statements)
0
17
0
Order By: Relevance
“…The reductions in fat mass were within the range observed in previous studies, which used other outcome measurements. 15,24,25 For the majority of the patients (4 out of 5), changes in fat mass followed the same patterns seen with body weight changes (3 patients showed reductions; 1 patient showed an increase). A positive correlation was observed between the percentage change in body weight and percentage change in fat mass, suggesting that lower fat mass, as a result of localized fat reduction using cryolipolysis, may contribute to overall changes in body weight.…”
Section: Discussionmentioning
confidence: 54%
“…The reductions in fat mass were within the range observed in previous studies, which used other outcome measurements. 15,24,25 For the majority of the patients (4 out of 5), changes in fat mass followed the same patterns seen with body weight changes (3 patients showed reductions; 1 patient showed an increase). A positive correlation was observed between the percentage change in body weight and percentage change in fat mass, suggesting that lower fat mass, as a result of localized fat reduction using cryolipolysis, may contribute to overall changes in body weight.…”
Section: Discussionmentioning
confidence: 54%
“…In addition, a previous clinical trial had shown reduction of superficial fat through sonographic devices, photographic appraisal, and caliper measurement [20]. A previous descriptive study of 170 Asian cases reported a 5.3 (1.7) mm (23.2%) reduction in fat thickness by high-resolution ultrasonography after cryolipolysis to the abdomen [21]. In addition, sonographic evaluation of intraabdominal adipose tissue yields a coefficient of variation of 64%; therefore, a previous paper did not recommend ultrasound for the assessment of VAT [22].…”
Section: Discussionmentioning
confidence: 99%
“…The further studies conducted by several authors evidenced the proposed effectiveness for fat reduction in human subjects. It was found that, in general, cryolipolysis causes a 22% reduction of subcutaneous fat thickness when used on the abdomen or flanks, i.e., the most frequent body parts treated by traditional SAL [42][43][44][45][46][47][48][49]. However, although these body parts' efficacy is relatively high, cryolipolysis solely focuses on the reduction of fat tissue, limiting its application and versatility.…”
Section: Discussionmentioning
confidence: 99%